2011
DOI: 10.1074/jbc.m110.149732
|View full text |Cite
|
Sign up to set email alerts
|

A Glutamine Residue Conserved in the Neurotransmitter:Sodium:Symporters Is Essential for the Interaction of Chloride with the GABA Transporter GAT-1

Abstract: Neurotransmitter:sodium symporters are crucial for efficient synaptic transmission. The transporter GAT-1 mediates electrogenic cotransport of GABA, sodium, and chloride. The presence of chloride enables the transporter to couple the transport of the neurotransmitter to multiple sodium ions, thereby enabling its accumulation against steep concentration gradients. Here we study the functional impact of mutations of the putative chloride-binding residues on transport by GAT-1, with the emphasis on a conserved gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 31 publications
5
51
0
Order By: Relevance
“…3, f and g). It is also noteworthy that the recent discovery (27)(28)(29) of residues involved in Cl Ϫ binding in GAT-1 and SERT suggests that residues Tyr-233 (TM2), Gln-473, and Ser-477 (TM6) together with Asn-509 and Ser-513 (TM7) are likely to perform equivalent roles in GlyT2 (Fig. 4a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3, f and g). It is also noteworthy that the recent discovery (27)(28)(29) of residues involved in Cl Ϫ binding in GAT-1 and SERT suggests that residues Tyr-233 (TM2), Gln-473, and Ser-477 (TM6) together with Asn-509 and Ser-513 (TM7) are likely to perform equivalent roles in GlyT2 (Fig. 4a).…”
Section: Resultsmentioning
confidence: 99%
“…4b), which lacks the hydroxyl necessary for the coordination of the Cl Ϫ ion and may prevent Cl Ϫ binding. Because a hydroxyl at this relative position is highly conserved in SLC6 transporters (27)(28)(29), the S513I substitution is predicted to interfere with glycine transport by disrupting the both Cl Ϫ (directly) and Na ϩ (indirectly) interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell Surface Biotinylation-Labeling of wild type and mutant transporters at the cell surface, using Sulfo-NHS-SS-Biotin (Pierce), quenching the reaction, cell lysis, and isolation of the biotinylated proteins by streptavidin-agarose beads (Pierce) were done as described (17). After SDS-PAGE (10% gel) and transfer to nitrocellulose, the GAT-1 protein was detected with an affinity-purified antibody, directed against an epitope from the cytoplasmic C-terminal tail of GAT-1, at a 1:500 dilution, with horseradish peroxidase-conjugated secondary antibody at a 1:40,000 dilution, and with ECL.…”
Section: Methodsmentioning
confidence: 99%
“…eral of the homologous residues are critical for transport in GAT-1 (12)(13)(14)(15)(16)(17), it is likely that the formation of the thin gate is an obligate intermediate during substrate translocation: the transition from the outward-to the inward-facing conformation. We have recently shown that perturbation of this thin gate of GAT-1 by mutation increases the proportion of outwardfacing transporters (6).…”
mentioning
confidence: 99%